Narrowing the Gap: Preserving Repertoire Diversity Despite Clonal Selection during the CD4 T Cell Response - Merkenschlager, Julia; Kassiotis, George (Frontiers in Immunology, 2015)
T cell immunity relies on the generation and maintenance of a diverse repertoire of T cell antigen receptors (TCRs). The strength of signaling emanating from the TCR dictates the fate of T cells during development, as well as during the immune response. Whereas development of new T cells in the thymus increases the available TCR repertoire, clonal selection during the immune response narrows TCR diversity through the outgrowth of clonotypes with the fittest TCR. To ensure maintenance of TCR diversity in the antigen-selected repertoire, specific mechanisms can be envisaged that facilitate the participation of T cell clonotypes with less than best fit TCRs. Here, we summarize the evidence for the existence of such mechanisms that can prevent the loss of diversity. A number of T cell-autonomous or extrinsic factors can reverse clonotypic hierarchies set by TCR affinity for given antigen. Although not yet complete, understanding of these factors and their mechanism of action will be critical in interventional attempts to mold the antigen-selected TCR repertoire.